Hydroxyl‐Rich Deep Eutectic Solvents Assistant Synthesis of VPO and Its Application in Selective Oxidation of n‐Butane. Issue 23 (17th June 2020) - Shi, Yanan; Dai, Fei; Zhang, Ting; He, Bin; Zhang, Ruirui; Liu, Ruixia; Ren, Baozeng
Abstract: Deep eutectic solvents (DESs) consisting of choline chloride (ChCl) and polyols (Ethylene glycol (EG), 1, 4‐Butanediol (BDO), Glycerol (GL), and Xylitol (XYL)) as a green and effective promoter assisting the synthesis of vanadium phosphorus oxide (VPO) were innovatively proposed and investigated in detail for the selective oxidation of n‐butane to maleic anhydride (MA). The catalytic results showed that the performance of VPO catalysts was improved significantly with the addition of polyols DESs. A combination of techniques including SEM, TEM, XRD, FT‐IR, Raman, XPS, and TG‐DTA were employed to investigate the effect of DES on the structure of VPO. We correlated the structure of the catalysts with catalytic performance and found that the n‐butane conversion was positively correlated with the intensity ratio of I (020) /I (204) for catalysts, and the MA selectivity of VPO catalysts was negatively correlated with the vanadium average oxidation state on the catalyst surface. Abstract : The hydroxyl‐rich DES make the VPO catalyst overcome the "trade off" effect, improve n‐butane conversion and MA selectivity simultaneously. The catalyst structure and catalytic performance are correlated. The results show that the conversion rate of n‐butane is positively correlated with the I (020) /I (204) relative intensity of the VPO catalyst, while the selectivity of MA is negatively correlated with the average valence state of V on the catalyst surface.